If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = y(x + y + 19) Reorder the terms: 3x = y(19 + x + y) 3x = (19 * y + x * y + y * y) Reorder the terms: 3x = (xy + 19y + y2) 3x = (xy + 19y + y2) Solving 3x = xy + 19y + y2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1xy' to each side of the equation. 3x + -1xy = xy + 19y + -1xy + y2 Reorder the terms: 3x + -1xy = xy + -1xy + 19y + y2 Combine like terms: xy + -1xy = 0 3x + -1xy = 0 + 19y + y2 3x + -1xy = 19y + y2 Reorder the terms: 3x + -1xy + -19y + -1y2 = 19y + -19y + y2 + -1y2 Combine like terms: 19y + -19y = 0 3x + -1xy + -19y + -1y2 = 0 + y2 + -1y2 3x + -1xy + -19y + -1y2 = y2 + -1y2 Combine like terms: y2 + -1y2 = 0 3x + -1xy + -19y + -1y2 = 0 The solution to this equation could not be determined.
| 5(v-9)-1=-7(3v+7)-v | | 11=3(v-3)-7v | | (A+6)+((A+2)+6)=(3A)+6 | | -13=3x-7 | | 2.1x+45.2+3.2-8.4x= | | 6x+12y=20 | | 14x*7=5x-6x | | -8x+4(x+6)=20 | | 5(4n-8)=-28+8n | | -3(r+4)=-41 | | k+4-7=3 | | 2.1x+45.2+3.2-824x= | | -16w+7.38=-16.7w+2.97 | | 7y+49=9(y+7) | | 7r-6r=5 | | 20=10v-5v | | 6=-6u+4(u+4) | | 6m-2=32 | | 0.3x=0.09 | | 6(x+3)=3(8+4x)-6 | | 20-14s=-20-19s | | 2-15-5=12 | | 4(x-3)+5=53 | | 4(2w-3)=2(3w+5) | | t^3+6t^2=25t+150 | | 3(X-2)=Xm+7 | | 5x+6=2x-2 | | 14=-5y+3(y-2) | | 18y=-20+19y | | -17-4k=3k+13-5k | | 0=-7r-3r | | 3(2x+5)=-37+22 |